Construction of an Amperometric Pyruvate Biosensor Based on Enzyme Bound to A Nanocomposite and Its Comparison with Enzyme Nanoparticles Bound to Electrode - Malik, Mansi; Chaudhary, Reeti; Pundir, C. S. (International Journal of Applied Sciences and Biotechnology, 2019)
An improved amperometric pyruvate biosensor was fabricated by immobilizing covalently commercial pyruvate oxidase (POx) from Aerococcus sps. onto nanocomposite of c-MWCNT (carboxylated multi- walled carbon nanotubes), copper nanoparticles (CuNPs) and polyaniline (PANI) electrodeposited onto gold (Au) electrode. The copper nanoparticles were prepared by chemical reduction method and characterized by transmission electron microscopy (TEM), UV- visible spectroscopy and X- ray diffraction (XRD). The working electrode (POx/c-MWCNT/CuNPs/PANI/AuE was studied via scanning electron microscopy (SEM), Fourier transform infrared spectrometry (FTIR) and electrochemical impedance spectroscopy (EIS) at different stages of its construction. The biosensor showed optimum activity at a pH of 5.0 and 35°C and a linearity for pyruvate in the concentration range, 0.1 µM to 2000 µM. The analytical recovery of added pyruvate was 99.6% and 99.2%. The within and between batch coefficients of variation (CV) were 0.052% and as 0.022% respectively. There was a commendable correlation between sera pyruvate values as measured by standard spectrophotometric method and the present method. The biosensor was applied to measure sera pyruvate level and compared with that biosensor based on pyruvate oxidase nanoparticles covalently bound to Au electrode.Malik et al. (2019) Int. J. Appl. Sci. Biotechnol. Vol 7(2): xxx-xxxGraphic AbstractSchematic representation of fabrication of POx/c-MWCNTs/CuNPs/PANI/AuE and electrochemical reactions involved in its response measurement (POx- Pyruvate oxidase; c-MWCNTs- Carboxylated multi-walled carbon nanotubes; CuNPs- Copper nanoparticles; PANI- Polyaniline; AuE- Gold electrode).